Supporting autonomy of nursing home residents with dementia in the informed consent process. (November 2019) - Beattie, Elizabeth; O'Reilly, Maria; Fetherstonhaugh, Deirdre; McMaster, Mitchell; Moyle, Wendy; Fielding, Elaine
Background: In studies involving people with dementia, researchers have historically defaulted to seeking consent from a proxy, the assumption being that people with dementia are unable to provide their own informed consent. This choice denies people with dementia a voice in the consent process, thus disregarding their autonomy and agency. Recently, other options for improving the consent process have been explored. Objective: This study aimed to determine whether nursing home residents with dementia could demonstrate an ability to provide their own informed consent as determined by the Evaluation to Sign Consent instrument. Methods: As part of a larger study on the quality of life of nursing home residents, the Evaluation to Sign Consent was administered to 392 people diagnosed with dementia. Data on demographic variables, such as gender and age, as well as level of cognitive impairment, were also collected. Results: Just over one-fifth (22%) of the residents with dementia were judged as having the capacity to provide their own informed consent to participate in this specific research project. Consistent with existing literature, capacity to consent was significantly, and negatively, associated with cognitive impairment. Conclusion: This study demonstrates that assuming all people diagnosed with dementia are unable to provide informed consent for research on the basis of cognitive test scores, or on clinical assessment alone, potentially denies them the autonomy to make a decision that they may be capable of making. Research involving people with mild-to-moderate dementia needs to consider evaluating whether potential participants have the capacity to provide their own consent.